'From technology adoption to consumption': Effect of pre-adoption expectations from fitness applications on usage satisfaction, continual usage, and health satisfaction. (September 2021) - Yousaf, Anish; Mishra, Abhishek; Gupta, Anil
Abstract: Despite the increasing usage of fitness applications, there is a dearth of research examining how expectations from fitness applications impact people's post-adoption consumption and health satisfaction. A novel research framework, spanning across pre- and post-adoption phases and involving a two-stage data collection, is proposed with additional contextual variables like technology self-efficacy, user-interface quality and perceived privacy, playing an important role in determining the continual usage for fitness applications and subsequent health satisfaction, shaped through pre-adoption expectations. Results of this work, conducted in India, not only enable an extension of the traditional adoption and post-adoption theories into the realm of fitness applications but also provide practitioners with guidance for developing fitness applications that enhance post-adoption engagement. Highlights: This work examines pre-adoption expectations shaping post-adoption health satisfaction. The context of the work is fitness applications. A two-stage data collection is executed. This work integrates elements of UTAUT with ECM in the domain of fitness. Health satisfaction is novel addition to these traditional IS theories.